Cover Picture: All‐Solution‐Processed, Ambient Method for ITO‐Free, Roll‐Coated Tandem Polymer Solar Cells using Solution‐Processed Metal Films (Energy Technol. 7/2014). Issue 7 (July 2014) - Angmo, Dechan; Dam, Henrik F.; Andersen, Thomas R.; Zawacka, Natalia K.; Madsen, Morten V.; Stubager, Jørgen; Livi, Francesco; Gupta, Ritu; Helgesen, Martin; Carlé, Jon E.; Larsen‐Olsen, Thue T.; Kulkarni, Giridhar U.; et al.
<x xml:space="preserve">Abstract</x> Roll with it: The cover image highlights an ambient slot–die coated Ag film onto which polymer solar cells (PSCs) are fabricated. Three different thicknesses of the same photoactive polymer are coated on the three different Ag stripes. The three stripes appear with three distinct colors due to the reflectivity of the underlying coated Ag film. Metal films bring several advantages including their reflectivity, low sheet resistance, and barrier properties. Until now, however, only evaporated metal films have been successfully utilized as electrode material in organic solar cells. In the Full Paper on page 651 ff., Frederik C. Krebs and colleagues at the Technical University of Denmark demonstrate the application of an ambient slot–die coated Ag film to roll‐processing of single‐ and tandem‐junction ITO‐free polymer solar cell devices. The slot–die coated Ag electrodes on Polyethylene terephthalate (PET) substrates are found to be superior to vapor‐deposited silver films in terms of roughness, and superior to comparable ITO films on PET in terms of flexibility. By employing only two simple roll‐to‐roll compatible processing methods in the fabrication of complete devices, including both electrodes (slot–die coating was used for up to 11 layers and flexo‐printing for the last counter electrode), large‐area single and tandem devices are demonstrated with fill factors (FF) exceeding 50 % in both types.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>